Reflections on slavery and the constitution - Anastaplo, George, 1925-2014 (Lexington Books, 2012)
In this insightful book about constitutional law and slavery, George Anastaplo illuminates both how the history of race relations in the United States should be approached and how seemingly hopeless social and political challenges can be usefully considered through the lens of the U.S. Constitution. He examines the outbreak of the American Civil War, its prosecution, and its aftermath, tracing the concept of slavery and law from its earliest beginnings and slavery's fraught legal history within the United States. Anastaplo offers discussions that bring into focus discussions.